Walter Benjamin And New Media - Volek, Jaromír (Communication Today, 2025)
The article deals with reading of Walter Benjamin’s works focused on new media. The article puts specific emphasis on the notions of ‘aura’ and ‘flaneur,’ two well-known themes in Benjamin´s scholarship. The article argues for the inseparability of old and new, modern and postmodern theory of media and illustrates their close connections in Benjamin’s texts. The author presents a sceptical view of the idea that the advent of digital new media is connected by necessity to a major historical break. He concludes that Benjamin’s theory of new media is highly useful for describing and understanding the current new media communication and subjectivity.